Synthesis of [Fe(Leq)(Lax)]n coordination polymer nanoparticles using blockcopolymer micelles - Göbel, Christoph; Klimm, Ottokar; Puchtler, Florian; Rosenfeldt, Sabine; Förster, Stephan; Weber, Birgit (Beilstein Journal of Nanotechnology, 2017)
Spin-crossover compounds are a class of materials that can change their spin state from high spin (HS) to low spin (LS) by external stimuli such as light, pressure or temperature. Applications demand compounds with defined properties concerning the size and switchability that are maintained when the compound is integrated into composite materials. Here, we report the synthesis of [Fe(Leq)(Lax)]n coordination polymer (CP) nanoparticles using self-assembled polystyrene-block-poly(4-vinylpyridine) (PS-b-P4VP) block copolymer (BCP) micelles as template. Variation of the solvent (THF and toluene) and the rigidity of the axial ligand Lax (Lax = 1,2-di(pyridin-4-yl)ethane) (bpea), trans-1,2-di(pyridin-4-yl)ethene (bpee), and 1,2-di(pyridin-4-yl)ethyne) (bpey); Leq = 1,2-phenylenebis(iminomethylidyne)-bis(2,4-pentanedionato)(2−)) allowed the determination of the preconditions for the selective formation of nanoparticles. A low solubility of the CP in the used solvent and a high stability of the Fe–L bond with regard to ligand exchange are necessary for the formation of composite nanoparticles where the BCP micelle is filled with the CP, as in the case of the [FeLeq(bpey)]n@BCP. Otherwise, in the case of more flexible ligands or ligands that lead to high spin complexes, the formation of microcrystals next to the CP–BCP nanoparticles is observed above a certain concentration of [Fe(Leq)(Lax)]n. The core of the nanoparticles is about 45 nm in diameter due to the templating effect of the BCP micelle, independent of the used iron complex and [Fe(Leq)(Lax)]n concentration. The spin-crossover properties of the composite material are similar to those of the bulk for FeLeq(bpea)]n@BCP while pronounced differences are observed in the case of [FeLeq(bpey)]n@BCP nanoparticles.
Keywords: block copolymer; composite; nanoparticles; self-assembly; spin crossover